Coherent Ising Machines with Optical Error Correction Circuits. Issue 11 (7th September 2021) - Reifenstein, Sam; Kako, Satoshi; Khoyratee, Farad; Leleu, Timothée; Yamamoto, Yoshihisa
Abstract: A coherent Ising machine (CIM) comprising a network of open‐dissipative quantum oscillators with optical error correction circuits is proposed. In the proposed network, the squeezed/anti‐squeezed vacuum states of the constituent optical parametric oscillators establish quantum correlations below the threshold through optical mutual coupling and collective symmetry breaking is induced above the threshold as a decision‐making process. This initial search process is followed by a chaotic solution search step facilitated by optical error correction feedback. The particular algorithm used by the proposed network is derived from the truncated Wigner stochastic differential equation. As an optical hardware technology, the proposed CIM has several unique features, including programmable all‐to‐all Ising coupling in the optical domain, directional coupling ( J i j ≠ J j i )‐induced chaotic behavior, and the ability to operate at low power at room temperature. The proposed CIM is evaluated in terms of its performance and how this scales at different problem sizes. It is shown that the various CIMs discussed in this paper are effective at solving many problem types, although the optimal algorithm depends on the problem case. It is further shown that the proposed optical implementations can be achieved with low energy consumption on thin‐film LiNbO3 platforms. Abstract : A coherent Ising machine comprising a network of open‐dissipative quantum oscillators with optical error correction circuits is proposed. This network can be used to solve combinatorial optimization problems, and it is shown that the system has high performance as a heuristic solver when simulated digitally.